2009
DOI: 10.1007/s10646-009-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of benzo(a)pyrene in Yangtze River source water with functional strains

Abstract: Degradation of benzo(a)pyrene (BaP) existing in the Yangtze River, used as source water for Nanjing City, China, was investigated with functional strains. The removal rates of BaP were 37.5, 20.8 and 70.8% for the three strains of the native bacterium NJ, and the two functional strains of Xhhh and Fhhh, respectively. The Fhhh specific degradation rate of BaP was 3.02 x 10(-6) day(-1), which was 1.9-fold of the rate with NJ and 3.7-fold of the rate with Xhhh. The concentrations of BaP in the source water, tap w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The two fusants simultaneously inherited high capacities of degradation, flocculation, and adaptation from its three parental strains. 10 The experimental results of biodegradation kinetics demonstrated that the functional strains were characterized with high biodegradation capacity of pharmaceutical and petrochemical, 11 which was further confirmed by a pilot study. 10 Our group also found that the fusants, obtained by IKPF, had excellent capacity of degrading lignin and pentachlorophenol.…”
Section: Introductionmentioning
confidence: 67%
“…The two fusants simultaneously inherited high capacities of degradation, flocculation, and adaptation from its three parental strains. 10 The experimental results of biodegradation kinetics demonstrated that the functional strains were characterized with high biodegradation capacity of pharmaceutical and petrochemical, 11 which was further confirmed by a pilot study. 10 Our group also found that the fusants, obtained by IKPF, had excellent capacity of degrading lignin and pentachlorophenol.…”
Section: Introductionmentioning
confidence: 67%
“…These properties stand against their ready microbial utilization and result into the need of a longer retention time for their biodegradation in bioreactors. In our previous study, more than 70% benzo(a)pyrene was removed in the biofilter cultured with functional microorganisms at an HLR of 3.0 m h −1 [11]. Recently, Cai et al [25] has reported that a tricklebed air biofilter had a high efficiency (over 90%) in removing methyl ethyl ketone, toluene, methyl isobutyl ketone and styrene, with empty bed retention time of no less than 2 min.…”
Section: Effects Of Hlr On Removal Of Svocsmentioning
confidence: 89%
“…Each filter was packed with 2.3 l granular activated carbon (GAC) supported by 1.1 l sand. The parameters related to biofilter design were previously described in detail [11]. The influent water of each biofilter was collected from the effluent of a pilot-scale sand filtration tank in Beihekou water plant.…”
Section: Operation Of Biofiltersmentioning
confidence: 99%
“…So far, few studies have been conducted to investigate the health risk reduction in drinking water treatment plants. Our previous studies have shown that biofilters can effectively remove the SVOCs in drinking water, but the health risk induced by some PAEs and PAHs in the finished water cannot reach safety levels (Zhang et al 2009(Zhang et al , 2012.…”
Section: Effects Of Water Treatment Processes On Reduction In Health mentioning
confidence: 99%